THz Streaking of the Autoionization Dynamics of O2 at the Free-Electron-Laser FLASH - Liu, Y. F.; Schnorr, K.; Schmid, G.; Augustin, S.; Meister, S.; Lindenblatt, H.; Rudenko, Artem; Kuebel, M.; Burger, C.; Stojanovic, N.; Treusch, Rolf; Duesterer, S.; et al. (Journal of Physics: Conference Series, 2017)
With a XUV-pump/THz-probe scheme the decay of excited O2 cations that were produced by irradiation with XUV photons has been investigated using a Reaction Microscope (ReMi) at the free-electron-laser FLASH in Hamburg. The temporal profile of electrons emitted due to autoionization of Rydberg states C4Σu- (nlσg) has been traced using THz streaking. This way the relaxation dynamics was followed. The relative shift in phase between photoelectrons and autoionization electrons was analyzed with respect to emission time delays or autoionization lifetimes.
CRIS-Team Scopus Importer:2023-04-20